A new DNA polymerase species from Drosophila melanogaster: a probable mus308 gene product. - Oshige, M.; Aoyagi, N.; Harris, P.V.; Burtis, K.C.; Sakaguchi, K. (Mutation Research, 1999)
Harris et al. [P.V. Harris, O.M. Mazina, E.A. Leonhardt, R.B. Case, J.B. Boyd, K.C. Burtis, Molecular cloning of Drosophila mus308, a gene involved in DNA cross-link repair with homology to prokaryotic DNA polymerase I genes, Mol. Cell. Biol., 16 (1996) 5764-5771.] reported the molecular cloning of Drosophila mus308 gene, and its nucleotide and protein sequences similar to DNA polymerase I. In the present study, we attempted to find and isolate the gene product by purifying a DNA polymerase fraction not present in mus308 flies. A new DNA polymerase with properties different from those of any known polymerase species was identified and partially purified from the wild-type fly embryos through ten column chromatographies. The enzyme was resistant to aphidicolin, but sensitive to ddTTP and NEM. Human proliferating cell nuclear antigen (PCNA) and Drosophila replication protein A (RP-A) did not affect the polymerase activity. It preferred poly(dA)/oligo(dT) as a template-primer. The molecular mass was about 230 kDa with a broad peak region of 200 to 300 kDa in HiPrep16/30 Sephacryl S-300 gel filtration. These properties a different from those of all reported Drosophila polymerase classes such as alpha, beta, gamma, delta, epsilon and zeta and closely resemble those of the gene product expected from the nucleotide sequence. The new polymerase species appears to have ATPase and 3'-5' exonuclease activities as shown by the chromatographies.